Some New Dynamic Inequalities Involving Monotonic Functions on Time Scales - S. H. Saker; E. Awwad; A. Saied (Journal of Function Spaces)
In this paper, we prove some new dynamic inequalities involving C- monotonic functions on time scales. The main results will be proved by employing Hölder’s inequality, integration by parts, and a chain rule on time scales. As a special case when T=R, our results contain the continuous inequalities proved by Heinig, Maligranda, Pečarić, Perić, and Persson and when T=N, the results to the best of the authors’ knowledge are essentially new.